2020
DOI: 10.1007/s10437-020-09377-8
|View full text |Cite
|
Sign up to set email alerts
|

The Early and Middle Holocene Lithic Industries of Ifri n’Etsedda (Eastern Rif, Morocco)

Abstract: Archaeological research has been carried out in the Eastern Rif (Morocco) since 1995 by a collaborative Moroccan-German research team. A major topic of the project is the transition from hunting-gathering to food production and related cultural developments. Innovations such as pottery and domesticated species appeared around 7.6 ka calBP. The cultivation of cereals and pulses is evident at that time. Two of the most important sites in the area are Ifri Oudadane and Ifri n’Etsedda. Both provide Epipaleolithic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The so-called "polisher shells" appeared in both Epipaleolithic and Neolithic layers, although their function is not yet clear. The analysis of the stone tools from Ifri Oudadane and Ifri n'Etsedda also support settlement and cultural continuity during the transition from the Epipaleolithic to the Early Neolithic (Broich et al 2020;Linstädter et al 2015).…”
Section: Discussionmentioning
confidence: 80%
“…The so-called "polisher shells" appeared in both Epipaleolithic and Neolithic layers, although their function is not yet clear. The analysis of the stone tools from Ifri Oudadane and Ifri n'Etsedda also support settlement and cultural continuity during the transition from the Epipaleolithic to the Early Neolithic (Broich et al 2020;Linstädter et al 2015).…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, the north African origin hypothesis still remains to be demonstrated, especially if we consider the significant distance between the Gibraltar strait and the core area of the Upper Capsian technocomplex (Perrin et al 2020), in eastern Algeria and Tunisia. Recent studies from the northern Morocco sites of Ifri Oudadane (Linstädter et al 2015) and Ifri n’Etsedda (Broich et al 2021) have reported assemblages with few trapezes and microburins, among other kind of armatures such as triangles of backed bladelets within thick sedimentary deposits considered “Epipalaeolithic.” However, nowadays such evidence remains inconclusive to establish a clear link with the Mesolithic of trapezes documented in the south of the Iberian Peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…Narrower and asymmetric shapes are also found in the Mesolithic of Alentejo, along the Atlantic coast of Portugal (Soares et al 2018), although the arrival of the Neolithic witnessed the widespread adoption of segments with abrupt retouches (Soares et al 2016). These are the most characteristic hunting weapon in the southern Iberian early Neolithic (Cortés Sánchez et al 2012;Rodríguez-Rodríguez et al 2013), alongside segments with abrupt retouches on the Mediterranean coast of Africa (Broich et al 2020), as attested in Ifri n'Etsedda (Eastern Rif). Within this context, the geometric microliths in El Retamar and Embarcadero de río Palmones, which are inspired by Mesolithic traditions, are exceptional.…”
Section: Microliths Geometric Flakes/arrowheadsmentioning
confidence: 95%